2003
DOI: 10.1186/1476-5918-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The purpose of this study was to determine the effects of hypoxic training on the cardiorespiratory system and skeletal muscle among well-trained endurance athletes in a randomized cross-over design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This finding is also consistent with other studies where training was associated with faster reoxygenation after repeated sprints, whether 2 × 15-s sprint with 15-s recovery (Buchheit and Ufland, 2011 ; Delextrat et al, 2018 ) or 5 × 30-s sprint with 4-min recovery (Jones et al, 2015 ). A faster increase in SmO 2 post-effort suggests that the O 2 supply/O 2 consumption balance is being restored more rapidly, and it has been suggested that the main factors accounting for such change are improved muscle oxidative capacity (Puente-Maestu et al, 2003 ), muscle blood flow and capillarization (Kime et al, 2003 ). These adaptations of the peripheral system may very well have taken place during the kayak-specific 3-weeks training camp.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with other studies where training was associated with faster reoxygenation after repeated sprints, whether 2 × 15-s sprint with 15-s recovery (Buchheit and Ufland, 2011 ; Delextrat et al, 2018 ) or 5 × 30-s sprint with 4-min recovery (Jones et al, 2015 ). A faster increase in SmO 2 post-effort suggests that the O 2 supply/O 2 consumption balance is being restored more rapidly, and it has been suggested that the main factors accounting for such change are improved muscle oxidative capacity (Puente-Maestu et al, 2003 ), muscle blood flow and capillarization (Kime et al, 2003 ). These adaptations of the peripheral system may very well have taken place during the kayak-specific 3-weeks training camp.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sea-level training, IHT has the potential to induce a further physiological strain 68 and specific molecular adaptations, 11 12 69 though not necessarily associated with improved exercise capacity. The rationale of using IHT relies on the hypothesis that these muscle adaptations surpass those triggered by normoxic exercise.…”
Section: Current Trends: Is It Time To Move Beyond Iht?mentioning
confidence: 99%
“…The present results confirm these findings and together highlight muscle reoxygenation capacity as an important factor of the ability to reproduce mechanical performance in subsequent sprint repetitions. The recovery of phosphocreatine and muscle reoxygenation after exercise presents similar kinetics (Chance, Dait, Zhang, Hamaoka, & Hagerman, 1992;Kime et al, 2003;McCully et al, 1994), and it has been reported that hyperoxia accelerates phosphocreatine resynthesis (Haseler, Richardson, Videen, & Hogan, 1998;Hogan, Richardson, & Haseler, 1999). It is therefore probable that a better muscle reoxygenation in HYP would have translated into a better PCr resynthesis during the recovery periods and a higher PCr availability for subsequent sprints.…”
Section: Hyperoxia and Arterial And Muscle Oxygenationmentioning
confidence: 89%